RANCANG BANGUN MESIN PENCETAK TUSUK SATE MENGGUNAKAN TEKNOLOGI DOUBLE ROLL UNTUK MENINGKATKAN PRODUKSI TUSUK SATE DI DESA KRASAK - Sukroni, Sukroni; Ghozali, Muhammad; Gunawan, Leo Van (P3M Politeknik Negeri Indramayu, 2025)
The expansion of the market or need for satay skewers has resulted in micro, small and medium enterprises producing satay skewers, especially in Krasak Kualahan village, to meet consumer needs. In Krasak village, micro, small and medium businesses still use traditional methods to process bamboo into skewers. However, this method requires a long time. Therefore, this machine was created to help skewer production businesses speed up the production process. By making a skewer printing machine using Double Roll technology, it will help businesses to increase production results. Double Roll technology is a technology that utilizes two rolls that are close together to produce thrust. The way this skewer molding machine works is by inserting bamboo pieces 50mm wide and 0.8mm thick, 22 cm long between the rollers that coincide with each other. This machine has 2 knife functions, namely flattening and forming uses an AC electric motor as a driver with specifications 1Phase 1HP 1400RPM.